Inflammation-Driven Breast Tumor Cell Plasticity: Stemness/EMT, Therapy Resistance and Dormancy - Baram, Tamir; Rubinstein-Achiasaf, Linor; Ben-Yaakov, Hagar; Ben-Baruch, Adit (Frontiers in Oncology, 2021)
Cellular heterogeneity poses an immense therapeutic challenge in cancer due to a constant change in tumor cell characteristics, endowing cancer cells with the ability to dynamically shift between states. Intra-tumor heterogeneity is largely driven by cancer cell plasticity, demonstrated by the ability of malignant cells to acquire stemness and epithelial-to-mesenchymal transition (EMT) properties, to develop therapy resistance and to escape dormancy. These different aspects of cancer cell remodeling are driven by intrinsic as well as by extrinsic signals, the latter being dominated by factors of the tumor microenvironment. As part of the tumor milieu, chronic inflammation is generally regarded as a most influential player that supports tumor development and progression. In this review article, we put together recent findings on the roles of inflammatory elements in driving forward key processes of tumor cell plasticity. Using breast cancer as a representative research system, we demonstrate the critical roles played by inflammation-associated myeloid cells (mainly macrophages), pro-inflammatory cytokines [such as tumor necrosis factor α (TNFα) and interleukin 6 (IL-6)] and inflammatory chemokines [primarily CXCL8 (interleukin 8, IL-8) and CXCL1 (GROα)] in promoting tumor cell remodeling. These inflammatory components form a common thread that is involved in regulation of the three plasticity levels: stemness/EMT, therapy resistance and dormancy. In view of the fact that inflammatory elements are a common denominator shared by different aspects of tumor cell plasticity, it is possible that their targeting may have a critical clinical benefit for cancer patients.